PENGARUH PENYULUHAN KESEHATAN DAN KESELAMATAN KERJA TERHADAP TINGKAT PENGETAHUAN DAN SIKAP NELAYAN DI DESA HATIVE BESAR - Mahani Ngidiho; Petriana Mahmud (STIKES Pasapua Ambon, 2019)
Introduction: Occupational health and safety are all conditions and factors that can impact occupational safety and health for the workforce and others in the workplace. High low levels of knowledge can cause a person’s attitude good or bad so that triggers the occurrence of marine accidents during work such as ship fires, drowning to inflict casualties or illness due to work such as illness In the joints or pain caused by the frequent occurrence of the night breeze. The purpose of this research is to see there is an extension of occupational safety health to the level of knowledge and attitude of fishermen in Hative Besar Village. Method: This research is a pre experimental design method with data collection Wilcoxon signed rank. The population is all fishermen in the Hative Besar village. Sampling using a quota sampling technique with sampel amounted to 92 people. Result: The results of research obtained from 92 respondents, namely there is a difference between before and after given health counseling on the knowledge and attitude of fishermen in Hative Besar Village with p value (p = 0,000). Conclusion: There is an effect of health counseling to level of knowledge and the Fisherman attirude in Hative Besar Village.